Scientists Negotiate Boundaries Between Religion and Science - Ecklund, Elaine Howard; Park, Jerry Z.; Sorrell, Katherine L. (Journal for the scientific study of religion, 2011)
Analysis of interviews with 275 natural and social scientists at 21 elite U.S. research universities suggests that only a minority of scientists see religion and science as always in conflict. Scientists selectively employ different cultural strategies with regards to the religion-science relationship: redefining categories (the use of institutional resources from religion and from science), integration models (scientists strategically employ the views of major scientific actors to legitimate a more symbiotic relationship between science and religion), and intentional talk (scientists actively engage in discussions about the boundaries between science and religion). Such results challenge narrow conceptions of secularization theory and the sociology of science literature by describing ways science intersects with other knowledge categories. Most broadly the ways that institutions and ideologies shape one another through the agency of individual actors within those institutions is explored.